PELESTARIAN DAERAH ALIRAN SUNGAI (DAS) PAKERISAN HULU BERBASIS PERANAN MASYARAKAT - Wiasta, I Wayan; Susrama, I Nengah; Astuti, Putu Sri (Jurnal Advokasi, 2016)
Subak has been set become Cultural Landscape World Heritage Site by UNESCO on June 29, 2012, so that Subak became the center of attention by the government or other institutions. The results showed that (1) Public DAS Pakerisan Hulu still patterned agrarian (2) Identified a number of roles that society can play as a buffer DAS Pakerisan particularly focused on conservation measures, (3) Terinventarisasi a number of restrictions to be shunned society for the preservation of the watershed Pakerisan, ( 4) Sistematic form of community unity as a buffer that is Pesuka Dukaan Pakerisan DAS DAS Wewidangan Pakerisan Hulu, (5) formulated draft pararem/awig-awig Pakerisan watershed areas as a means of regulating the behavior of people who are oriented to the preservation of the watershed Pakerisan.